Pendampingan Mahasiswa Universitas Mandiri dalam Kompetisi Subang Innovation Festival 2.0 - Asep Priatna; Ina Marlina; Aji Fauziana Ridwan; Permono Adi Putro (Abdibaraya, 2026)
The problem of honey adulteration in Indonesia has shown an increasing trend based on scientific findings and media reports, causing losses for farmers and consumers and highlighting the need for rapid, accurate, user-friendly, and affordable detection technology. This community service activity aimed to assist students in the Subang Innovation Festival (SIF) 2025 while developing NECTROSCAN (Nectar Electro-Scan Analyzer), a honey authenticity detection device based on electrical profiles and fuzzy logic designed to support farmers’ needs. The mentoring process was conducted through six stages, including idea formulation and prototype design, proposal development, administrative and substance selection, Top 10 presentation, Top 5 presentation and visitation, as well as awarding and exhibition, which involved intensive consultation, technical testing, market needs analysis, and validation by BP4D Subang and the Appropriate Technology Research Center of BRIN. The results indicate that students successfully identified real problems faced by honey farmers in Subang, designed and developed a prototype based on conductivity sensors and fuzzy logic, and presented their innovation systematically and convincingly to internal and external evaluators. The prototype received positive feedback and was considered to have strong potential as appropriate technology, leading the team to place third in the competition. This activity improved students' competencies in applied research, data-driven problem-solving, scientific communication, and cross-sector collaboration, while producing innovations relevant to and applicable to community needs